Applying active thermography in the non-destructive investigation of historical objects = Zastosowanie termowizji aktywnej do badań nieniszczących obiektów zabytkowych - Nowak, Henryk; Noszczyk, Paweł (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper pertains to the problem of historic building envelope investigation with the use of active thermography. Mainly emphasized is its application in the detection of different material inclusions in historic walls. Examples of active thermography in the reflective mode application and a description of the experimental investigation has been shown on a wall model with the inclusion of materials with significantly different thermal conductivity and heat capacity, i.e. styrofoam, steel and granite.
Keywords: przegroda budowlana; obiekty zabytkowe; wtrącenia materiałowe; building envelope; historic building; material inclusion